Reforms in the Education System of the Republic Of Uzbekistan to Improve the Management of Higher Education Institutions - Anvar Gafurov (Universitas Budi Luhur, 2024)
Abstrak: Artikel ini mengungkapkan reformasi utama di sektor pendidikan Republik Uzbekistan. Hingga tahun 2017, jumlah institusi pendidikan tidak cukup untuk mendaftarkan siswa Uzbek sekolah. Oleh karena itu, banyak siswa yang tidak mendaftar telah mulai mengejar keinginan pendidikan mereka di luar negeri, terutama di negara-negara tetangga, yaitu Kazakhstan, Kyrgyzstan, dan Federasi Russia. Bahkan data statistik menunjukkan bahwa sekitar setiap tahun hingga 2017, hanya 9 persen lulusan sekolah yang bisa mendaftar ke universitas, sisanya lulusan baru tidak dapat mendaftar. Sementara itu, populasi Uzbekistan meningkat secara dramatis. Oleh karena itu, tujuan utama artikel ini adalah untuk menunjukkan pentingnya dan kebutuhan reformasi di sektor pendidikan Uzbekistan. Informasi dalam artikel ini didasarkan pada analisis data sekunder, serta laporan statistik dan dokumen yang diperoleh dari berbagai kementerian dan lembaga pemerintah. Selain itu, korelasi demografi dan cakupan institusi ditunjukkan. Abstract: The article reveals the main reforms in the educational sector of the Republic of Uzbekistan. Until 2017, the number of educational intuitions was not enough to enroll Uzbek schools’ pupils. Therefore, many unenrolled pupils have started to pursue their educational desires abroad, especially in neighboring countries, namely Kazakhstan, Kyrgyzstan, and the Russian Federation. Even statistical data showed that approximately every year until 2017, only 9 percent of school graduates could have enrolled in universities; the rest of fresh graduates could not be enrolled. Whereas, the population of Uzbekistan has been raised dramatically. Therefore, the main purpose of this article is to show the importance and need for reforms in the education sector of Uzbekistan. The information inthis article is based on the analysis of secondary data as well as statistical reports and documents obtained from various government ministries and agencies. Moreover, the correlation between demography and coverage of intuitions has been shown.